Peranan Umkm (Usaha Mikro, Kecil Dan Menengah) Terhadap Perekonomian Indonesia - Sumarni Sumarni (Jurnal Manajemen FE-UB, 2017)
Small and Medium Enterprises are many business activities in demand after an economic crisis that impacts on layoffs big companies. SME sector support provides opportunities employment opportunities for the unemployed in the world of government work as well as medium and large companies. The aim of this study to find out the profile of SMEs in Indonesia, employment opportunities provided on the activities of SMEs, Contribution of SMEs to GDP. In this writing using descriptive method, do the analysis only until descriptive level, ie analyzing and presenting the facts systematically so it can be easier to understand and infer. Result of this study is: viewed from the profile of SMEs, the number of SMEs the most many engaged in trading and at least move on electricity and water; Number of SME entrepreneurs both men and women whose primary education is 7,597,595 people, at most Little Diploma III, that is as many as 252,049 people, in total amount male and female entrepreneurs are 22,513,552 persons; Contribution of SMEs in absorbing labor as much as 43,911,721 people, most in trade and at least in the electric field and drinking water; Contribution of SMEs in Broto Domestic Product isRp.1.648.555.770.662, -. Keywords: SME, Profile, Donation